The Automotive Chassis - Genta, Giancarlo (Springer, 2017)
The Automotive Chassis is the result of two decades of experience: On the one hand from the experience of teaching courses such as Vehicle Mechanics, Vehicle System Design, Chassis Design to engineering students; on the other hand from the design practice of vehicle and chassis components in a large automotive company. This work is addressed primarily to students of automotive engineering and secondarily to all technicians and designers working in this field. It is also addressed to all enthusiasts who are looking for a technical guide.